Study and Analysis on Biometrics and Face Recognition Methods - Singha, Anjani Kumar; Singla, Anshu; pandey, Rajneesh kumar (IJRDO -Journal of Computer Science Engineering, 2016)
— Human Biometrics is a rising technology, whichhas been broadly used in forensics, safe access and top-securityprison. A biometric system is primarily a pattern recognitionsystem that recognizes a person by determining the verificationby using his different biological features i.e. Fingerprint, retinascan,iris scan, hand geometry, and face recognition areimportant physiological biometrics and behavioral trait areVoice recognition, keystroke-scan, and signature-scan. In thispaper different biometrics techniques such as Iris scan, retinascan and face recognition techniques are discussed.